Best Approximations and Kolmogorov and Trigonometric Widths of the Classes B_p,θ^Ω of Periodic Functions of Many Variables - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain estimates exact in order for the best approximations and Kolmogorov and trigonometric widths of the classes B_p,θ^Ω of periodic functions of many variables in the space L^q for certain values of the parameters p and q.